2001
DOI: 10.1067/mnc.2001.109862
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of left ventricular function at rest and post-stress in patients with myocardial infarction: Evaluation with gated SPECT

Abstract: In patients with an earlier myocardial infarction, LV function post-stress may not represent the true resting LV function. Consequently, this result justifies the stratification of patients before starting the gated SPECT study. In patients with an earlier myocardial infarction, the gated acquisition should be performed during the rest study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…Patients with previous MI were excluded because LV volumetric parameters are often difficult to measure in those who have severe perfusion defects. 36 Indeed, the mean summed stress score was 8.7 and 5.2, and SDS was 1.4 and 1.1, respectively, in the initial study, which included patients with previous MI, and the current study, which excluded MI. 11 Furthermore, 23% of the patients had severe abnormal myocardial perfusion in the initial study, but only 12% of the patients had such a severe abnormality in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with previous MI were excluded because LV volumetric parameters are often difficult to measure in those who have severe perfusion defects. 36 Indeed, the mean summed stress score was 8.7 and 5.2, and SDS was 1.4 and 1.1, respectively, in the initial study, which included patients with previous MI, and the current study, which excluded MI. 11 Furthermore, 23% of the patients had severe abnormal myocardial perfusion in the initial study, but only 12% of the patients had such a severe abnormality in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the results reported previously by Bavelaar-Croon et al who found, using Tc-99m tetrofosmin, that 33 of 58 patients (57%) with sustained myocardial infarction showed statistically signifi cant deterioration of LV function (>2% decrease) that persisted as long as 30 min after stress. 28 In our study, it might be underestimated for the reversibility. In the fi xed defect group, there might be ischemia patients because of the rest images obtained 3 h after injection.…”
Section: Discussionmentioning
confidence: 89%
“…Oxygen consumption of tissue is usually higher in the subendocardium than in the subepicardium. 28 During stress, a relatively large imbalance between oxygen supply and demand in the subendocardial layers subtended by stenosed vessels may develop without signifi cant changes in the overall blood supply. This may lead to stunning and hence a decrease in LV function without signs of reversible ischemia on myocardial perfusion images.…”
Section: Discussionmentioning
confidence: 99%
“…A possible limitation of our study is that we employed a stress-rest protocol. Bavelaar-Croon et al demonstrated that LVEF derived at 30 min post-stress was significantly lower than that derived at rest in patients with early myocardial infarction [21]. They also indicated that there was no significant difference in LVEF between a post-stress and a resting condition in patients with a low likelihood of coronary disease.…”
Section: Discussionmentioning
confidence: 92%